2020
DOI: 10.1177/2325967120904012
|View full text |Cite
|
Sign up to set email alerts
|

Atelocollagen Injection Improves Tendon Integrity in Partial-Thickness Rotator Cuff Tears: A Prospective Comparative Study

Abstract: Background: Ongoing controversy surrounds the best treatment modality for partial-thickness rotator cuff tears.Purpose: To investigate the effects of atelocollagen injection in patients with small, symptomatic, intratendinous rotator cuff tears.Study Design: Randomized controlled trial; Level of evidence, 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 32 publications
0
46
1
1
Order By: Relevance
“…Histological and biomechanical studies in the rabbit model showed better results in the group that Proliferative phase Remodeling phase used atelocollagen to repair the rotator cuff tendon [7]. In a study by Kim et al [13], atelocollagen injection on human rotator cuff tendon tear was shown to improve the functional outcome and integrity of the tendon in intra-tendinous RCTs. Therefore, they suggested that type I atelocollagen injection is an optional treatment to delay tear progression and reduce tear size.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Histological and biomechanical studies in the rabbit model showed better results in the group that Proliferative phase Remodeling phase used atelocollagen to repair the rotator cuff tendon [7]. In a study by Kim et al [13], atelocollagen injection on human rotator cuff tendon tear was shown to improve the functional outcome and integrity of the tendon in intra-tendinous RCTs. Therefore, they suggested that type I atelocollagen injection is an optional treatment to delay tear progression and reduce tear size.…”
Section: Discussionmentioning
confidence: 99%
“…They introduced a bio-inducible collagen patch as a safe and effective treatment for cuff-healing of arthroscopic rotator cuff repair. However, several previously reported studies have cited several weaknesses, such as modeling in animals, small sample size, no control group, or studies involving only partial RCT [7,13,30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Protocols to produce atelocollagen with high purity at a faster speed have been developed in some studies [77]. In other studies, atelocollagen was used to treat tendons and periodontal tissues [78,79]. Additionally, some examples of improvement in collagen functions have been reported, including the enhancement in the ability of collagen to promote cell proliferation and anti-thrombogenic activity via conjugation with chondroitin sulfate.…”
Section: Types Of Ecm-based Materials For Biomedical Applicationsmentioning
confidence: 99%